Disruption Of Microbial Cell Morphology By Buxus Macowanii - Ngobeni, B.; Mashele, S.S.; Malebo, N.J.; van der Watt, E.; Manduna, I.T. (BMC Complementary Medicine and Therapies (2020) 20:266, 2020)
Background: Microbial infections are one of the major causes of death globally. This is attributed to the rising costs of primary healthcare and its inaccessibility especially in developing countries. Moreover, there has been an increase in microbial strains that have reduced susceptibility to antimicrobial drugs. Research on the antimicrobial properties of medicinal plants, which could address these problems, has become more important as they present fewer side effects when compared to the antibiotics currently in use. This study evaluated the antimicrobial properties of a methanolic extract from Buxus macowanii in order to assess its potential in the development of novel antimicrobial drugs. Methods: Antimicrobial activity of the extract was evaluated using the broth microdilution method. The effects of B. macowanii on the morphology of B. cereus were observed using Scanning and Transmission electron microscopy. Chemical profiling of the plant extract was performed using the GCMS. Results: The extract showed antimicrobial activity against all the microbial species used. Microscopic examination of the cells of B. cereus cells treated with Buxus macowanii showed some changes in morphology such as damage of the cell wall, swelling of the cells and incomplete cell division that eventually resulted in cell death. Neophytadiene, an antimicrobial compound was detected in the extract using GCMS. Conclusion: The morphological disruptions of the cell wall of Bacillus cereus explain the antimicrobial properties of B. macowanii and indicate its possible application in the development of natural antimicrobial drugs.
Article
Keywords: Antimicrobial activity; Buxus macowanii; Neophytadiene